Java tutor / Shanmuganathan Supramaniam - Shanmuganathan , Supramaniam (2005)
This documentation is an exercise submitted to the Faculty of Science Computer and Information Technology (FSCIT), University of Malaya as a report for the final year project and also as a fulfillment to Computer Science Degree Program in University of Malaya. In this document, it will explain about the Java Tutor project in detail. Java Tutor is a web-based courseware that is developed for anyone who is interested in learning Java programming language The Waterfall model with prototyping is used to develop Java Tutor system because it is simple and easy to understand. The programming language operation system, web server, web browser, database and the development tool that are used when developing this system are ASP.NET, MS IIS Server Internet Explorer, MS SQL Server, Microsoft Visual Studio .NET and Adobe Photoshop 7.0. It is hoped that the Java Tutor system will able to promote users interest toward Java programming language, which is a powerful programming language.